(3GdJMbjb aj GdfSH GdhKjb hGdGYJHGQ aj fSH GdfHj GdoeNJGQ hGdJYQja HCRhGLg hChdGOgs - (3CMeO Hf eMeO Hf CHj GdbGSe Hf CMeO Hf YHO GdQMef Gdecj GdYTeGhj,J (B1142 (3g` s ((3eQGcT s)
(3ChdgG (B:s
(3hHYO aEfj cfJ cKjQ GdThb HGdfHj Udi Gddg Ydjg hSde hHCUMGHg hChdGOg hMjf aGJfG GdCUd hde fOQc dg ReGfG aHMKfG fMf Ydi GdaQY s
(3BNQgG (B:s
(3hNJegG GdChd aj JGQjN QHjY GdfHhj YGe SHYI heGFJjf hCda hcGf GdaQZ ef fSNgG dfaSg GdMGL YHOGdbGOQ GdHhjMjGhj GdTQja GdEOQjSj HeQGcT s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B242 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B70s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B308 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B421 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B100 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs